Pengaruh Penerapan Pajak Progresif Kendaraan Bermotor Atas Berlakunya Perda Nomor 8 Terhadap Kepatuhan Wajib Pajak - Latrini, Made Yeni; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p29, 2018)
This study aims to determine the effect of the implementation of vehicle progressive tax on the enactment of Regulation No. 8 of 2016 on taxpayer compliance. Motor vehicle progressive tax is applied to increase revenue of Bali Province. Progressive taxes are imposed on ownership of four-wheeled vehicles or two-wheelers more than one based on identity cards.The population in this study are all taxpayers of motor vehicle owners who are subject to progressive tax. Technique of data collecting done through spreading of questioners. Data analysis techniques use simple linear regression.This study proves that the implementation of motor vehicle progressive tax on the enactment of Regional Regulation No. 8 of 2016 affect taxpayer compliance. Keywords: Progressive tax, taxpayer compliance.